Efficient spin filtering through cobalt-based extended metal atom chains. - Georgiev, V; McGrady, J (2010)
Density functional theory in conjunction with nonequilibrium Green's functions has been used to explore charge transport through the cobalt-based extended metal atom chain, Co(3)(dpa)(4)(NCS)(2). The isolated molecule has a doublet ground state, and the singly occupied sigma nonbonding orbital proves to be the dominant transport channel, providing spin filtering efficiencies in excess of 90%. The metal chain differs from typical organic conductors in that the pi orbitals that form the contact with the gold electrode are orthogonal to the transport channel. As a result, the rehybridization of these pi levels by the applied electric field has only a minor impact on the current, allowing spin filtering to persist even at biases in excess of 1 V.